JAK2 V617F and FLT3 ITD mutation in myelodysplastic syndrome - Radić Antolic, Margareta (Array, 2007)
Molecular basis of myelodysplastic syndrome (MDS) is characterized by a number of frequently occurring abnormalities. Cytogenetic abnormalities in MDS are among the most important routine parts of diagnosis and prognosis, but mutations like internal tandem duplication (ITD) in FLT3 gene and point mutation V617F in JAK2 gene may provide supplementary information. Since some forms of MDS show a significant overlap with chronic myeloproliferative disease (MDS classified as MDS/MPD-U) or acute myeloid leukemia (AML transformed from MDS), this prompted us to determine the prevalence of FLT3 ITD and JAK2 V617F mutations in patients with MDS. The study included a total number od 50 MDS patients classified according to the World Health Organization classification: 4 patients with refractory anemia (RA), 13 patients with myelodysplastic/myeloproliferative disease-unclassifiable (MDS/MPD-U), 4 patients with chronic myelomonocytic leukemia (CMMoL), 8 patients with RA with excess of blasts (RAEB) and 21 patients with secondary AML (AML transformed from MDS, but not therapy-related MDS). Analysis of bone marrow was done by conventional cytogenetic and fluorescence in situ hybridization (FISH) for del(5q), del(7q) and rearrangement of MLL gene. DNA and RNA were isolated from bone marrow cells or peripheral blood cells. The detection of JAK2 V617F was performed by allele specific PCR (Baxter et al, Lancet 2005) and FLT3 ITD by RT-PCR (Nakao et al, Leukemia 1996). Structural and numerical cytogenetic abnormalities were frequent in patients with secondary AML and RAEB as expected. There were no patients with isolated del(5q) or del(7q). Patients with CMMoL did not have any karyotypic abnormalities with exception of one patient with del(20q) and izo(17q). The presence of JAK2 V617F was detected in one of four patients with RA and one out of thirteen patients with MDS/MPD-U. There was no mutation detected in patients with RAEB, CMMoL or secondary AML. On the contrary, the only two positive FLT3 ITD patients were those with secondary AML. In conclusion, there is a need to analyze the mutational status of JAK2 and FLT3 gene in order to properly differentiate MDS/MPD-U and to predict possible transformation of MDS toward AML.